Ovarian tissue autotransplantation improves longevity in mice - Ruhliada, Nikolai N. (Frontiers in Physiology, 2024)
In the study we show the improvement in life longevity in mice experimental model after step-by step autologous ovarian transplantation and compare its effects with exogenic transdermal estradiol usage. This has proven to be more efficient than "traditional" hormonal replacement therapy. Despite the highest speed and effectiveness of estradiol replacement deficiency in blood by its oral or transdermal use, one did not receive a significant increase in the life longevity in animals and possibly in women. The function of transplanted fragment is usually limited to 6-12 months. This is enough for oncofertility purposes, sometimes, but not for longevity improvement. We performed periodical tissue return (autologous transplantation), containing both cortex and medulla in mice experimental model, that resulted in statistically reliable improvement of longevity. Our experience indicates the important role of medullary ovarian factors in slowing the aging process of the body and increasing the life expectancy in the experiment. As we showed, the transdermal estrogen supportive therapy in ovarian deficiency improves estrogen levels, but much slower decreases FSH and LH. As well as the best longevity we reached with step-by-step periodic ovarian autotransplantation, thus making "prosthetics" of ovarian function longer, than it is preplanned physiologically (direct correlation between the levels of FSH and lifespan (r=0,98)). The experimental model we suggested could be projected and to other mammals or humans, as the cortical transplantation gives the same results for reproduction restoration in mice and humans and even on hormone levels normalization, but there is still lack of information about anti-ageing factors containing in ovarian medulla and cortex. That is why we consider that the most important factor for anti-ageing ovarian transplantation technology is to preserve and transfer both medulla and cortex as parts of whole ovary.